Slippery slopes of stress: ordered failure events in German banking - Michael Koetter; Thomas Kick (Deutsche Bundesbank, 2007)
Outright bank failures without prior indication of financial instability are very rare. Supervisory authorities monitor banks constantly. Thus, they usually obtain early warning signals that precede ultimate failure and, in fact, banks can be regarded as troubled to varying degrees before outright closure. But to our knowledge virtually all studies that predict bank failures neglect the ordinal nature of bank distress. Exploiting the distress database of the Deutsche Bundesbank we distinguish four different distress events that banks experience. Only the worst entails a bank to exit the market. Weaker orders of distress are, first, compulsory notifications of the authorities about potential problems, second, corrective actions such as warnings and hearings and, third, actions by banking pillar's insurance schemes. Since the four categories of hazard functions are not proportional, we specify a generalized ordered logit model to estimate the respective probabilities of distress simultaneously. Our model estimates each set of probabilities with high accuracy and confirms, first, the necessity to account for different kinds of distress events and, second, the violation of the proportional odds assumption implicit in most limited dependent analyses of bank failure.
Keywords: G33; K23; L50; C35; G21; 330; Bank; failure; distress; generalized ordered logit; Bankinsolvenz; Universalbank; Bankrisiko; Ranking-Verfahren; Logit-Modell; Schätzung; Theorie; Deutschland